Prediction on CO2 and Nox reduction on micro gas turbine fed by different syngas quality - Fadhil S.S.A.; Hasini H.; Jaafar M.N.M.; Othman N.F. (Penerbit UTM Press, 2023)
The stringent requirement of power plant environmental emissions and the need to improve efficiency have led to significant rise of research in clean energy in this decade. Gas turbines are favourable in the power generating industries since it has environmental advantages besides capable to utilize variety of fuels like natural gas, fuel oils and synthetic gas. In recent years, the use of synthetic gas or syngas has been increasing due to its advantages such as CO2 and NOx emission reduction. Although many studies have been carried out in the area of syngas combustion, the study on the combustion characteristics and pollutant emission remains a challenge due to its complexity and limitless variety of fuel compositions involved. This paper presents the investigation of CO2 and NOx reduction on micro gas turbine combusting syngas with different methane compositions using computational fluid dynamics (CFD). The combustion trend of syngas is found to be similar to combustion with natural gas in general. However, the average temperature distribution is found to be very much dependent on the methane composition of the mixture. Higher methane composition is fuel results in higher average temperature distribution. The reduction of CO2 and NOx is predicted to be significant in combustion with syngas compared to conventional natural gas. 2015 Penerbit UTM Press. All rights reserved.